Deciding to peg the exchange rate in developing countries: the role of private-sector debt - Philipp Harms; Mathias Hoffmann (Deutsche Bundesbank, 2009)
We argue that a higher share of the private sector in a country's external debt raises the incentive to stabilize the exchange rate. We present a simple model in which exchange rate volatility does not affect agents' welfare if all the debt is incurred by the government. Once we introduce private banks who borrow in foreign currency and lend to domestic firms, the monetary authority has an incentive to dampen the distributional consequences of exchange rate fluctuations. Our empirical results support the hypothesis that not only the level, but also the composition of foreign debt matters for exchange-rate policy.
Keywords: E52; F31; F41; 330; Exchange rate regimes; foreign debt; monetary policy; Wechselkurssystem; Wechselkurspolitik; Auslandsverschuldung; Private Verschuldung; Ökonomischer Anreiz; Entwicklungsländer